Impact of Diabetes in COVID-19 Associated Mucormycosis and its Management: A Non-Systematic Literature Review - Rashid, Muhammed; Rajan, Asha K.; Thunga, Girish; Shanbhag, Vishal; Nair, Sreedharan (Current Diabetes Reviews, 2023)
Background: COVID-19 has become extremely dangerous manifesting itself in a variety of forms ranging from a simple flu-like illness to death. COVID-19 associated mucormycosis (CAM) is a global threat with diabetes being a major contributor. Objective: This review aims to give a clear picture of the impact of hyperglycemia in CAM along with its management. Methods: Google and Google Scholar were searched and studies that addressed the impact of diabetes in CAM were considered for this review. We also performed a bibliographic search of the specific article to find additional studies. Results: A series of events such as unregulated activation of innate immune system modification, pro-inflammatory M1 macrophages activation, and the depletion of natural killer cell activity is very common in patients with COVID-19. In addition, the exacerbated cytokine syndrome and hyperinflammatory response may elevate the severity of this condition, which further leads to higher mortality. The impaired immune phase which follows provide the niche for increased infection among diabetic patients making them more prone towards developing mucormycosis and associated infections. Early detection, surgical debridement, and appropriate medical treatment with antifungals and hypoglycaemic agents may help control the infection and associated morbidity and mortality. COVID-19 drugs, hypoglycaemic agents, antifungals, and comorbidities have all been associated with adverse side effects and drug interactions. Conclusion: Clinicians should be well aware of this deadly disease and manage COVID-19, diabetes, and mucormycosis through individualized treatment regimens to improve patient outcomes.
Keywords: COVID-19